Offline and computer‐based eLearning interventions for medical doctors' education - Semwal, Monika (2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The primary objective of this systematic review is to evaluate the effectiveness of offline computer‐based eLearning educational interventions compared to traditional classroom learning and/or other types of eLearning or no intervention, for improving medical doctors’ knowledge, skills, attitudes, satisfaction and patient‐related outcomes. We will assess the cost and cost‐effectiveness of offline computer‐based eLearning, and adverse, unintended, or undesirable effects of the interventions as secondary objectives.